Astrocytes and Microglia and Their Potential Link with Autism Spectrum Disorders - Petrelli, Francesco; Pucci, Luca; Bezzi, Paola (Frontiers in Cellular Neuroscience, 2016)
The cellular mechanism(s) underlying autism spectrum disorders (ASDs) are not fully understood although it has been shown that various genetic and environmental factors contribute to their etiology. As increasing evidence indicates that astrocytes and microglial cells play a major role in synapse maturation and function, and there is evidence of deficits in glial cell functions in ASDs, one current hypothesis is that glial dysfunctions directly contribute to their pathophysiology. The aim of this review is to summarise microglia and astrocyte functions in synapse development and their contributions to ASDs.